Entrepreneurship attitudes, need for achievement, and the intention of developing a business among public university students in Lima Metropolitana - Loli Pineda, Alejandro Erasmo (2012)
The objective of this study is to know the entrepreneurship attitudes, need for achievement, and the intention of developing a business among public university students in Lima Metropolitana. The study selected a sample of 657 students belonging to many majors, between the first semester and the tenth one. The findings show us that the most of the students have a positive attitude to creativity and entrepreneurship. By the same token, there is a strong relationship between the entrepreneurshipattitudes to start a new business and the need for achievement. However, that relationship diminishes when it is analyzed the relationship between the need for achievement and the intention of developing a new business. In the same way, an analysis of entrepreneurship total score and its components shows that there is a positive and significant correlation among all of them. Regarding the demographic, social, and their relationship to the entrepreneurship (low, normal, high); it is not found that there are significant differences when it is compared the data form different universities,and the only exception appears when working experience of the subjects is analyzed on the other hnad, there is not a significant association among variables such as age, gender, marital status, and the study level.